Replacing fish meal with alternative protein sources in common carp’s feed - Adekoya, Abidemi; Porcadilla, Maridell; Varga, Dániel; Kucska, Balázs (Acta Agraria Kaposváriensis, 2018)
The objective of this study was to investigate the effect of PL68 and soybean meal as alternative protein sources in the diet of common carp (Cyprinus carpio L.). The experiment lasted for four weeks. There was a significant difference (p
Keywords: fish meal; fish meal replacement; soybean; PL68; common carp